How do trade liberalization and gender inequality affect economic development? - Fatima Farooq; Imran Sharif Chaudhry; Shazia Khalid; Muhammad Tariq (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2019)
This study examines the relationship between trade liberalization, gender inequality and economic development in 18 selected developing countries over the time period from 1993 to 2017. Panel ARDL approach has been employed to examine the relationship among variables. The results of the study suggest that trade openness and gender inequality in education and employment, and female to male ratio have negative impact on GDP per capita in developing countries. Based on these results and keeping in view the importance of trade openness and gender equality for economic development, this study is useful to suggest that export led trade policy and provision of equal opportunities to both male and female in education and employment should be adopted in order to achieve higher levels of economic development and for bringing gender equality in all economic activities.
Keywords: 330; trade liberalization; gender inequality in education; gender inequality in employment; GDP per capita; ARDL approach